Molecular Control of Cardiac Fetal/Neonatal Remodeling - Ross A. Breckenridge (Journal of Cardiovascular Development and Disease, 2014)
Immediately following birth, the mammalian heart switches from generating ATP via glycolysis to β-oxidation of lipid. Coincident with this metabolic remodeling, cardiomyocyte mitosis ceases and regenerative capacity is lost. Recently, our understanding of the molecular pathways linking physiological stimuli with gene expression and phenotype changes around birth has increased, although fundamental gaps remain. This review discusses recent work that sheds light on this important area of mammalian cardiovascular development.